2018
DOI: 10.1038/s41598-018-20499-7
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol mitigates Endoplasmic Reticulum Stress Induced Cell Death by targeting caspase 3/7

Abstract: The Endoplasmic Reticulum (ER) plays a fundamental role in executing multiple cellular processes required for normal cellular function. Accumulation of misfolded/unfolded proteins in the ER triggers ER stress which contributes to progression of multiple diseases including neurodegenerative disorders. Recent reports have shown that ER stress inhibition could provide positive response against neuronal injury, ischemia and obesity in in vivo models. Our search towards finding an ER stress inhibitor has led to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 71 publications
(67 reference statements)
2
29
0
Order By: Relevance
“…B). We have previously showed the bioactivity of KFL in ameliorating ER stress‐induced cell death with a reduction in the expression level of ER stress markers in IMR32 cells upon pretreatment with KFL . Our present study showed that KFL increased the expression of IRE1α without activating ER stress in IMR32 cells.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…B). We have previously showed the bioactivity of KFL in ameliorating ER stress‐induced cell death with a reduction in the expression level of ER stress markers in IMR32 cells upon pretreatment with KFL . Our present study showed that KFL increased the expression of IRE1α without activating ER stress in IMR32 cells.…”
Section: Resultssupporting
confidence: 68%
“…Kaempferol (KFL) is a phytoestrogen that belongs to the class of flavonoids and is known to exhibit antioxidant, anti‐inflammatory, and anticancer activities . In our attempt toward identifying an inhibitor against ER stress‐induced cell death, we found KFL to rescue mammalian cells from apoptosis induced by multiple cell death inducers by acting as an allosteric inhibitor for executioner caspases . While performing the experiments we observed changes in morphology of IMR32 cells, a human neuroblastoma cell line with neurite like outgrowths, upon prolong incubation in the presence of KFL.…”
Section: Introductionmentioning
confidence: 99%
“…4B). We have previously showed the bioactivity of kaempferol in ameliorating ER stress induced cell death with a reduction in the level of ER stress markers expression in kaempferol pretreated conditions in IMR32 cells (Abdullah and Ravanan, 2018a). Our present study showed that kaempferol increases the expression of IRE1α without activating ER stress in IMR32 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Kaempferol is a phytoestrogen belongs to the class of flavonoids and known to exhibit antioxidant, anti-inflammatory and anti-cancer activity (Wang et al, 2018). In our attempt for identifying an inhibitor against ER stress induced cell death, we found kaempferol to rescue mammalian cells from apoptosis induced by multiple cell death inducers by acting as an allosteric inhibitor for executioner caspases (Abdullah and Ravanan, 2018a). While performing the experiments we observed the change in morphology of IMR32 cells, a human neuroblastoma cell line with neurite like outgrowths upon prolong incubation in the presence of kaempferol.…”
Section: Introductionmentioning
confidence: 99%
“…The evidences demonstrated that kaempferol enhances lipophagy through induction of AMPK/mTOR signaling pathway, resulting in decreased ER stress and subsequently, a reduction in cell injury. Kaempferol can exert neuroprotective effect by regulation of ER stress (Abdullah & Ravanan, ). Again, kaempferol provides an inhibitory impact on GRP78 and CHOP expression to reduce ER stress.…”
Section: Kaempferol and Er Stressmentioning
confidence: 99%